EXPLORING EMOTION MANAGEMENT TO IMPROVE SANTRI DISCIPLINE IN PESANTREN: AN ANGER MANAGEMENT PERSPECTIVE - khoir, Muhammad ilzamul; Lawal, Uthman Shehu; Baharun, Hasan (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study explores the emotional management of pesantren administrators as the first step in fostering santri by utilizing anger management as a synergy between emotional management and discipline. The approach used in this research is qualitative with a case study type to understand how to shape discipline values. The research findings show that in shaping the Santri discipline, administrators need to manage emotions positively, understand emotion recognition to help better manage reactions to situations and use relaxation techniques to reduce stress and improve concentration. In addition, it is essential to identify problems, look for alternatives, choose the best solution, speak clearly, honestly, and politely, change mindsets from negative to more positive or realistic, create a comfortable workspace and maintain healthy relationships with others. The results of this study provide a deep understanding of the spirit of discipline; these findings become a specific place in helping and developing a new face of an administrator and become a reference for other institutions, especially pesantren, by expressing emotion management.